THE HYDROXYAPATITE OF QUAIL EGGSHELLS (CORTURNIX COTURNIX) AS REMINERALIZATION MATERIALS IN PRIMARY TEETH (IN VITRO) - Yasmin, Ulfa; Sapitri, Indah (Universitas Baiturrahmah, 2025)
Introduction: Caries is the most common oral health problem particularly among children. Calcium deficiency due to demineralization of the enamel could be anticipated with application of remineralization materials. One of the natural alternatives to support remineralization process is quail eggshells (Coturnix coturnix) containing high calcium carbonate as hydroxyapatite precursor. Objective: This study aims to evaluate the effectiveness of quail eggshells as hydroxiapatite materials. Methods: This study was a laboratory experimental study with pretest-posttest control group design. The sample of this study was 15 mandibular primary insisivus teeth were mounted on self cure acrylic resin, and were divided into 3 groups, the treatment group used 20% quail eggshells gel (Group A), the positive control group used CPP-ACP (Group B), and the negative control used placebo gel (Group C). The applications were conducted 30 minutes for 14 days and immersed in artificial saliva. The enamel hardness was measured using Vickers Hardness Tester. Data were analyzed using Paired T-Test and Post Hoc LSD. Result: The result of Paired T-Test showed that all the groups was statistically significant (p<0,05) that leads to remineralization process. Post hoc LSD showed that the significantly difference at posttest occurred between the treatment group againts the both control groups (p<0,05). Conclusion: It can be concluded that 20% quail eggshells gel is effective as remineralization materials in primary teeth.